2023
DOI: 10.3390/membranes13010072
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Silica-Polyacrylonitrile Nanohybrids for Water Treatments

Abstract: In this work, the removal of NOM (natural organic matter) as represented by humic acid by means of electrospun nanofiber adsorptive membranes (ENAMs) is described. Polyacrylonitrile (PAN) was used for the preparation of ENAMs incorporating silica nanoparticles as adsorbents. The addition of silica to the polymer left visible changes on the structural morphology and fibers’ properties of the membrane. The membrane samples were characterized by pure water permeability, contact angle measurement, SEM, XPS, and XR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…Malczewska et al reported that the inclusion of silica particles in the spinning solution decreases the fiber diameter, however enhanced the antibacterial and mechanical properties. 45 The top views of all of the nanofibers were randomly aligned on each layer, which is in accordance with FTIR and XRD graphs.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Malczewska et al reported that the inclusion of silica particles in the spinning solution decreases the fiber diameter, however enhanced the antibacterial and mechanical properties. 45 The top views of all of the nanofibers were randomly aligned on each layer, which is in accordance with FTIR and XRD graphs.…”
Section: Resultssupporting
confidence: 75%
“…The inclusion of silica particles can act as a nucleation site for phase separation or polymer crystallization, leading to a finer nanofiber structure and confirming the polymer chain during fiber formation. Malczewska et al reported that the inclusion of silica particles in the spinning solution decreases the fiber diameter, however enhanced the antibacterial and mechanical properties . The top views of all of the nanofibers were randomly aligned on each layer, which is in accordance with FTIR and XRD graphs.…”
Section: Resultsmentioning
confidence: 99%
“…This approach makes it possible to impart hydrophobic properties to PAN-based materials while maintaining the inherent vapor-and air-permeability of PAN, which is required for textile, medical purposes, and the production of fabrics with special-purpose and self-cleaning materials [7][8][9]. In addition, modification of PAN with silicon-containing components is used in the production of membranes and filters to change their permeability and selectivity [10][11][12][13][14]. A surface modification of PAN fibers with silicon-containing coupling agents to improve compatibility with the matrix in the manufacture of the polymer composites was investigated in [15].…”
Section: Introductionmentioning
confidence: 99%
“…SiO 2 is used as a silicon-containing modifier component, and composite fibers obtained by electrospinning [7,14,[18][19][20][21], often, simultaneously with achieving the required special characteristics demonstrate inhomogeneous morphology due to the formation of large aggregates [7,8,12,14,20], that could decrease mechanical properties [12,22].…”
Section: Introductionmentioning
confidence: 99%